The study on Sarawak remote area solar energy application problems - Kolot, A. (Universiti Malaysia Sarawak, UNIMAS, 2002)
This study is conducted on the Samusan National Park, Tanjung Datu National Park and Talang-Talang besar Island. The focus of this study is to identify the problems associated with application of solar energy for remote area electrification.